Examining the relationships among body image dissatisfaction, exercise motives and exercise behaviors in home-based exercise participants - Calanog, Dana V. 1999-
Physical inactivity has been one of the problems dealt with by different individuals around the world, this is potentially heightened by the restrictive measures implemented during the onset of the COVID-19 Pandemic. The presence of a pandemic can alter the daily regimen of individuals, including one’s fitness routine. The COVID-19 Pandemic is one such example, wherein social distancing restrictions were imposed along with the closing down of sports and fitness facilities. These conditions made the place of residence the main place of activity with a choice of adapting a home-based exercise routine. The study seeks to explore individuals who adapted home-based exercise participation in the COVID-19 Pandemic as there has been scarce data in their exercise behavior and experiences, specifically body image dissatisfaction and its association with exercise motives and behavior. The study’s main objective is to determine the association of body dissatisfaction score and exercise motives to the exercise behavior of home-based exercise participants, specifically those who started a home-based exercise routine in any period of the COVID-19 Pandemic and continues to subscribe to it until the present, using the concepts in the Self-Determination Theory. The study used a cross-sectional quantitative research design . Study results found that home-based exercise participants have lower Body areas Satisfaction Scale (BASS) scores, Relative Intrinsic Goal Score (RIGS), and Leisure Score Index (LSI) compared to gym-based exercise participants; BASS and LSI which are statistically significant for difference of means between the two exerciser groups. Home-based exercisers also presented higher percentage of body dissatisfied individuals and higher percentage of insufficiently active individuals compared to gym-based exercise participants. Goal contents across exerciser groups showed that intrinsic-health is the most dominant goal content of exercise subscale, followed by the intrinsic-skill, and extrinsic- image subscales. In testing the relationships of the main variables, only Body Areas Satisfaction Scores and Relative Intrinsic Goal Score significant positive moderate correlation. In looking at the multiple regression analysis on the effect of BASS and RIGS to LSI with consideration to exerciser group, there is insufficient evidence that BASS, RIGS can significantly predict LSI of exerciser groups. Exploring the goal contents subscale and its relation to LSI, only intrinsic-skill subscale was found to have a significant weak positive correlation to LSI of the samples. Simple linear regression showed that LSI can be significantly predicted by the intrinsic-skill subscale of the goal contents of exercise.